Meningoencephalitis Due to HIV Replication Despite Plasmatic Viral Control - Dinh, Aurélien; Salomon, Jérôme; Du, Damien Le; Mathez, Dominique; Carlier, Robert; Bernard, Louis; Truchis, Pierre de (Journal of the International Association of Physicians in AIDS Care (Chicago, Ill. : 2002), 2011)
We report a symptomatic case of HIV replication in CSF (Cerebro Spinal Fluid) despite low plasmatic viral load. The patient, known HIV positive since 3 years, under HAART (Highly Active Antiretroviral therapy), presented an acute meningoencephalitis which was improved by optimization of treatment for a better CNS (Central Nervous System) penetration according to the CHARTER's (CNS HIV Antiretroviral Therapy Effects Research) score. CNS can be considered as a specific compartment for HIV replication and can be involved in acute or chronic neurologic impairment. As showed in this observation, CHARTER score could be helpful to optimize HAART penetration in CNS, but indication and use remain uncertain in current practice.